(Im)mobilities and Precarity in Lawrence Hoba’s The Trek and Other Stories (2009). - Matanga , Sarah Yeukai (Imbizo, 2025)
This article draws on Butler and Standing’s theories of precarity to explore questions of land, citizenship, and belonging in Lawrence Hoba’s collection of short stories, The Trek and Other Stories (2009). An exploration of these themes is important in unpacking the complexities of movements related to the post-2000 Fast Track Land Reform Programme (FTLRP) in Zimbabwe. The article explores Hoba’s depiction of the various and complex mobilities engendered by the land redistribution process as tied up with ambivalent and precarious notions of home. Through a close reading of a cross-section of short stories in Hoba’s collection, the article examines how precarity is intricately connected to the concept of mobility and argues that insecurities spawned by movements triggered by the land reform can foster resilience and radical thinking in some of the characters. The study is situated at the intersections of precarity theory and mobilities studies. This transdisciplinary theoretical framework allows a comprehensive and nuanced exploration of the dynamics of belonging within a post-2000 Zimbabwean context. By engaging mobilities and precarity lens to read Hoba’s text, the article seeks to yield fresh insights into the messiness of mobility as a liberation praxis.